PENGARUH KOMPOS KOTORAN SAPI TERHADAP PERTUMBUHAN DAN HASIL KEDELAI (Glycine max (L.) Meril) PADA KONDISI CEKAMAN AIR (Cattle Waste Compost Effect on the Growth and Yield of Soybean (Glycine Max (L.) Meril) on Water Stress Condition) - Yusiana Asih Lestari; Nerty Soverda; Nyimas Myrna Elsa (Bioplantae, 2012)
Soybean is one of the much-needed agricultural commodities in Indonesia. Jambi provinces in particular the many problems encountered in soybean cultivation is marginal land conditions. Most of the soybean done on dry land. Generally it reacts acidic soil with Al++ high status, low cation exchange capacity, soil water content and low nutrient. Such land could be improved by adding organic matter, one of them by giving cow manure compost on soybean. This study aimed to see the effect of composted cow manure on the growth and yield of soybeans grown in conditions of water stress. This research was conducted at the Experimental Farm Faculty of Agriculture, University of Jambi. The design used in this study was completely randomized design with one factor. The treatment in this study is the provision of compost manure with various doses of 0 (without giving cow manure compost), 10 tons ha-1 compost manure, 20 tons ha-1, compost manure, 30 tons ha-1 and 40 tons ha-1 compost manure. The results of this study indicate that administration of composted cow manure in conditions of water stress did not significantly affect plant height, canopy dry weight, root dry weight and outcome variables, namely the number of pods per plant, number of pods per plant and weight containing 100 seeds and crop yield.Keywords: Soybean, compost, water stress